Clinical Pharmacokinetics, Safety and Exploratory Efficacy Study of a Topical Bactericidal VB-1953: Analysis of Single and Multiple Doses in a Phase I Trial in Acne Vulgaris Subjects - Jain, Shilpi; Yadav, Vishal; Bhatia, Neal (Clinical drug investigation, 2020)
Background and Objective Cutibacterium acnes is a key pathogenic factor in the development of acne vulgaris. Topical and oral antibiotics play a pivotal role in effective management of the disease. The emergence of resistance to the currently available antibiotics poses a serious set-back to this algorithm, and the reduced arsenal can diminish the efficacy of treatment. A novel formulation of VB-1953 (2%) topical gel has been developed with dual mechanism of action and bactericidal activity, unlike the currently approved antibiotics, which are bacteriostatic agents, targeting acne vulgaris. The objective was to check the clinical pharmacokinetics, safety and tolerability of single and multiple doses of VB-1953 in adult subjects with facial acne vulgaris, when applied twice daily (every 12 h) for about 15 days starting from Day 1, morning dose until Day 15, morning dose. Methods This was a Phase 1 open-label study of VB-1953 for evaluation of pharmacokinetics, safety, tolerability and exploratory efficacy in otherwise healthy adult patients with moderate-to-severe facial acne vulgaris. The 12 subjects (aged 18–45 years) enrolled for the study applied VB-1953 (2%) gel twice daily for 15 days on the entire face every 12 h starting from Day 1 morning to Day 15 morning. Pharmacokinetic assessment was evaluated by sequential blood collection and safety was measured by assessments of local skin reactions (LSRs). Results Plasma concentrations of VB-1953 indicate a low systemic exposure. By Day 2, steady-state was achieved and by Day 15 maximum plasma concentration ( C max ) was 0.4640 ng/mL indicating about twofold increase upon multiple dosing. Changes in safety parameters (vital signs, electrocardiogram, physical examinations, hematology, chemistry, urinalysis) were clinically insignificant. Conclusion VB-1953 topical gel appears to be safe for use in adults with facial acne vulgaris and may offer new advances as a topical antibiotic agent for the disease.